As artes da gestão ordinária : subespécies de capital simbólico no cotidiano de trabalho - Santos, Mariana Aparecida Euflasino dos (2021)
In this thesis I aimed to understand how they can be (re)known subspecies of symbolic capital, in the everyday management of street vendors in the municipality of Maringá -PR. For this, I proposed a reflection, from the theoretical lenses of Michel de Certeau on the arts of making the everyday and the perspective of symbolic capital in the context of Pierre Bourdieu's theory of practice. As a methodological path I adopted ethnography. I had as methodological reference Geertz's interpretative perspective (2015) and the approach of urban ethnography. I then sought to weave links between the "box" of theoretical tools and the ethnographic method. It was therefore a question of considering the possibility of plurality of the concept of capital, but above all discussing the possibility of bringing the understanding of capital closer to the reality of simple management, which happens in small businesses and which is distant from the dominant and traditional managerial models of administration. Thus, ordinary man, when performing in his work practice the ordinary and intuitive management, uses different subspecies of symbolic capital, other than the predominant economic or valued in its meaning in mainstream administration. I dared, therefore, to indicate paths for the recognition of possible subspecies of symbolic capital that inhabit the "vulgar", and therefore the "non-distinct", in the context of street workers. Thus, I followed and lived the experience of the practice of work in the daily life of street vendors in the municipality of Maringá-PR, seeking to understand its practices and effects. As I experienced the power relations that went through those daily work practices and with the basis of the theoretical and methodological tools, I realized a micro-construction of the social space studied and then I interpreted, in the specific context of this micro social space, the predominance of three subspecies of symbolic capital: a) economic capital materialized in popular good (sub-products), b) social capital as sub-networks, and c) linguistic capital as popular orality. These form a symbolic representation next to the "fabric" of symbolic capital interpreting them in the immersion of the context of ordinary management. So, they are resources managed in motion of resistance enterprises and survive that differ from other management realities. In addition, I have interrogated in this study the need to consider the mediation of the "ways of doing" as a strategic tactic in the context of ordinary management. Finally, the conclusions draw notes on the results raised from the problem and the proposed objectives.